Long-range transport of dust enhances oceanic iron bioavailability - Kenlee, Bridget; Owens, Jeremy D.; Raiswell, Robert; Poulton, Simon W.; Severmann, Silke; Sadler, Peter M.; Lyons, Timothy W. (Frontiers in Marine Science, 2024)
Wind-borne dust supply of iron (Fe) to the oceans plays a crucial role in Earth's biogeochemical cycles. Iron, a limiting micronutrient for phytoplankton growth, is fundamental in regulating ocean primary productivity and in turn the global carbon cycle. The flux of bioavailable Fe to the open ocean affects oscillations in atmospheric CO2 due to its control on inorganic carbon fixation into organic matter that is eventually exported to the sediments. However, the nature of dust-delivered Fe to the ocean and controls on its bioavailability remain poorly constrained. To evaluate the supply of wind-borne bioavailable Fe and its potential impact on Fe-based climate feedbacks over the last 120,000 years, we examine sediment profiles from four localities that define a proximal to distal transect relative to Saharan dust inputs. Bulk δ 56 Fe isotope compositions (average = -0.05‰) and FeT/Al ratios suggest crustal values, thus pointing to a dominant dust origin for the sediments at all four sites. We observed no variability in grain size distribution or in bioavailable Fe supply at individual sites as a function of glacial-versus-interglacial deposition. Importantly, there is no correlation between sediment grain size and Fe bioavailability. Spatial trends do, however, suggest increasing Fe bioavailability with increasing distance of atmospheric transport, and our sediments also indicate the loss of this Fe and thus potential bioavailability utilization once deposited in the ocean. Our study underscores the significance of Fe dynamics in oceanic environments using refined speciation techniques to elucidate patterns in Fe reactivity. Such insights are crucial for understanding nutrient availability and productivity in various ocean regions, including the Southern Ocean, where wind-delivered Fe may play a pivotal role. It is expected that dust delivery on glacial-interglacial timescales would be more pronounced in these high-latitude regions. Our findings suggest that studies linking Fe availability to marine productivity should benefit significantly from refined Fe speciation approaches, which provide insights into the patterns and controls on Fe reactivity, including atmospheric processing. These insights are essential for understanding the impacts on primary production and thus carbon cycling in the oceans and consequences for the atmosphere.